THEORY OF PLANNED BEHAVIOR UNTUK MEMPREDIKSI NIAT BERINVESTASI - Seni, Ni Nyoman Anggar; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017DO - 10.24843/EEB.2017.v06.i12.p01, 2017)
Planned behavior theory as the theoretic foundation for knowing the influence of attitudes toward behavior, perceptive behavior control and subjective norm on the objective of the young generation to stock investment in the capital market. The data are collected by questionnaires distributed to 395 respondents. Hypotheses are tested with Partial Least Squares (PLS). Exploratory test is done first to determine the indicators in this research. The result shows that perspective toward behavior, perceptive behavior control and subjective norm positively and significantly affect the objective of the young generation to stock investment in the capital market